KANDUNGAN MIKROBA PADA PENYEDAP MADIDIHANG - Fadila; Yuliyanti Kasim; Juhartini; Sitti Salmiyah A. Bahruddin (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Yellowfin tuna flavoring is processed from yellowfin tuna (Thunnus albacores) into fish powder. Natural flavoring is attractive and very useful for reducing MSG intake, which is nutritious and safe for public consumption. If this product is in powder form, if it is stored for a long time, it may experience changes in microbiological quality. The purpose of this study was to determine the microbial content of Yellowfin Yellowfin Flavor (Thunnus albacores). This research was conducted at the Food Technology Science Laboratory, Department of Nutrition, Ministry of Health Polytechnic and Laboratory of PT. Saraswanti Indo Genetech, Bogor. The results of this study indicated that the microbial content of salmonella sp. in the simplo and duplo tests was negative, meaning that the sample did not detect salmonella sp. and the content of mold in yellowfin flavoring after 6 months of storage is classified as very low, namely <10 colonies/gram. It was concluded that this product is safe from salmonella sp negative and mold after 6 months of storage.